Flashed Müller-Lyer and Poggendorff Virtual Illusions. (May 2021) - Anstis, Stuart; Cavanagh, Patrick
A moving frame can dramatically displace the perceived location of stimuli flashed before and after the motion. Here, we use a moving frame to rearrange flashed elements into the form of classic illusions. Without the moving frame, the initial arrangement of the flashed elements has no illusory effect. The question is whether the frame-induced displacement of position precedes or follows the processes underlying the illusions. This illusory offset of flashed chevrons does generate a Müller-Lyer illusion and the illusory offset of two line segments does create a Poggendorff illusion. We conclude that the site where the frame-induced position shift emerges must precede the site at which the Müller-Lyer and Poggendorf illusions arise.